2014
DOI: 10.1159/000363390
|View full text |Cite
|
Sign up to set email alerts
|

New Inhaler Devices - The Good, the Bad and the Ugly

Abstract: Drug delivery to the lungs is an effective way of targeting inhaled therapeutic aerosols and treating obstructive airway diseases, such as asthma and chronic obstructive pulmonary disease (COPD). In the past 10 years, several new drugs for the management of asthma and COPD have been marketed and more are under development. These new therapeutic respiratory drugs have been furthered by innovations in all categories of pulmonary drug delivery systems to ensure optimal aerosolisation performance, consistency in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
139
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(149 citation statements)
references
References 52 publications
0
139
0
2
Order By: Relevance
“…It is also likely that Swiss physicians almost systematically add the second layer of patient education/information reported in this survey as an anticipatory response to this perceived lack of efficiency. It has been repeatedly shown that health care providers (across all disciplines) often do not sufficiently master the inhalation technique themselves (7,11,18,19) and are not sufficiently aware of device-specific handling difficulties, even more so in an increasingly complex environment with a steadily growing inhaler diversity (11,13,(20)(21)(22). In this context, the best person to provide inhaler training should be the one with the appropriate skills, adequate time, and access to teaching resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also likely that Swiss physicians almost systematically add the second layer of patient education/information reported in this survey as an anticipatory response to this perceived lack of efficiency. It has been repeatedly shown that health care providers (across all disciplines) often do not sufficiently master the inhalation technique themselves (7,11,18,19) and are not sufficiently aware of device-specific handling difficulties, even more so in an increasingly complex environment with a steadily growing inhaler diversity (11,13,(20)(21)(22). In this context, the best person to provide inhaler training should be the one with the appropriate skills, adequate time, and access to teaching resources.…”
Section: Discussionmentioning
confidence: 99%
“…The available inhaler devices share common potential sources of handling errors. In addition, pressurized metered-dose inhalers (pMDI) and dry-powder inhalers (DPI) have specific requirements that may lead to additional errors in daily practice (7,13,14). Finally, the patient should ultimately be adherent and compliant with the prescribed therapy, which can be best achieved through better understanding of his medical history and comorbidities, cultural environment, health behaviors, and preferences (15).…”
Section: Introductionmentioning
confidence: 99%
“…5 A number of different breathactuated devices are available. 33 They contain a conventional pressurised canister which is actuated by a spring mechanism. The devices sense the patient's breath and trigger the spring to release the dose as the patient inhales allowing the two actions to be automatically co-ordinated.…”
Section: Pmdis = Pressurised Metered Dose Inhalersmentioning
confidence: 99%
“…The ideal device to be used by a COPD patient has a universal design, is independent of patient inspiratory force and can deliver a consistent and reproducible dose into the lungs with patient compliance [57].…”
Section: Indacaterol/ Glycopyrronium: Choosing the Right Devicementioning
confidence: 99%